Assessment of correlation between electrogoniometer measurements and sports-specific movement in karate elites - Lotfian, S.; Safarcherati, A.; Jamshidi, A.; Sanjari, M. A. (Asian Journal of Sports Medicine, 2014)
Purpose: To examine the intra-rater reliability of knee movement data in sagital plane obtained from electrogoniometer (EGM) in a basic, sport-specific task of karate.